2015
DOI: 10.1038/eye.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy ab interno (trabectome): yet another possibility in the treatment of uncontrolled glaucomatocyclitic crisis under systemic valganciclovir therapy?

Abstract: Purpose To assess the outcome of trabectome surgery in the treatment of glaucomatocyclitic crisis (Posner-Schlossman syndrome) in patients with uncontrolled intraocular pressure (IOP). Patients/Methods Trabectome surgery was performed in seven patients with diagnosed glaucomatocyclitic crisis and uncontrolled IOP where cytomegalovirus DNA was verified by polymerase chain reaction in aqueous humour samples. All patients were treated with oral valganciclovir. After surgery the patients were followed-up for 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Three eyes (12.5%) lost ≥2 lines of BCVA due to cataract progression after XEN‐45 stent implantation, likely secondary to the use of postoperative steroid eye drops. Despite the material of the XEN‐45 implant being soft and tissue‐conforming, implant exposure occurred in two eyes (8.3%) in our study and has also been reported previously …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Three eyes (12.5%) lost ≥2 lines of BCVA due to cataract progression after XEN‐45 stent implantation, likely secondary to the use of postoperative steroid eye drops. Despite the material of the XEN‐45 implant being soft and tissue‐conforming, implant exposure occurred in two eyes (8.3%) in our study and has also been reported previously …”
Section: Discussionsupporting
confidence: 85%
“…Despite the material of the XEN-45 implant being soft and tissue-conforming, implant exposure occurred in two eyes (8.3%) in our study and has also been reported previously. 25,28,29 Our study was limited by the small number of patients. There was insufficient statistical power to identify the predictors of failure.…”
Section: Discussionmentioning
confidence: 99%
“…An affected individual's vision will be determined by the level of associated corneal edema, ranging from visual acuity as high as 20/20 to vision being limited to light perception [2]. The pupil will often be slightly dilated and sluggishly reactive to light [2,7]. The conjunctiva may demonstrate no abnormalities or can demonstrate ciliary flush [2].…”
Section: Figure 1: Eye Schematic Depicting the Mechanism For The Elevmentioning
confidence: 99%
“…The conjunctiva may demonstrate no abnormalities or can demonstrate ciliary flush [2]. On slit-lamp examination, discrete, round, white keratic precipitates on the endothelium can be noted [2,4,7,8]. PSS will usually have significantly elevated IOP, potentially leading to corneal epithelial edema [1,2,4,7,8].…”
Section: Figure 1: Eye Schematic Depicting the Mechanism For The Elevmentioning
confidence: 99%
See 1 more Smart Citation